A Green pH‐switchable Amino Acid Based Smart Wormlike Micellar System for Efficient and Controlled Drug Delivery. Issue 3 (30th January 2017) - Lone, Mohd Sajid; Bhat, Parvaiz Ahmad; Shah, Rais Ahmad; Chat, Oyais Ahmad; Dar, Aijaz Ahmad
Abstract: A biocompatible and biodegradable amino‐acid based anionic surfactant system has been formulated which self assembles into wormlike micelles in presence of NaCl and displays excellent sol‐gel transition under pH stimulus. The surfactant synthesized was Sodiumtetradecanoyl Phenyl Alanine (STDPA). The micellar solution behaves as sol at /below pH 8.25 and transforms into gel at /above pH 8.65, exhibiting sol‐gel transition in a very narrow pH range. This pH triggered sol‐gel transition shows excellent reversibility upon recurrent changes in pH. Steady and dynamic rheological experiments reveal that the solution at/above pH 8.65 is viscoelastic due to the formation of wormlike micelles (WLMs) and was Newtonian at/below 8.25 due to the presence of spherical micelles. The microstructural evolution was further validated by Dynamic Light Scattering and Cryo TEM imaging. Further, the formulation was used to study the release of drug Ibuprofen (IBU) at these two pHs. IBU release from the material depends on pH of the release medium and occurs without any burst release at pH 8.65. Abstract : pH switchable wormlike micellar system for the efficient and controlled delivery of Ibuprofen (IBU) drug at two pHs viz, 8.25 and 8.65 is studied. The formulation at pH 8.25 shows burst release of the encapsulated drug while as at a pH of 8.65 it shows delayed release of the encapsulated drug.